PENERAPAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR AKUNTANSI SISWA - Pudji Lestari, (Pendidikan Ekonomi, 2009)
The research is intended to describe the teachers activity and that of the students, and the students improvement in learning achievement. This classroom action research was carried out in three cycles, each of which consisted of four stages. The subject comprised 40 students, and the object was the application of the contextual learning. The instrument consisted of observation sheet, test, and questionnaire.  The data were analyzed descriptively.  The results showed that the teachers competence in managing the class improved.  The students activity and learning achievement improved in every cycle.